Pengaruh Green Satisfaction, Green Knowledge dan Green Trust terhadap Keputusan Pembelian Produk Skintific (Studi Kasus : Mahasiswa FEB UNISMA Angkatan 2021) - Monteha, Karisma; Asiyah, Siti; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of green satisfaction, green knowledge and green trust on the purchase decision of Skintific products. Purchase decisions are part of consumer behavior that includes choosing, buying, and using a product. This study uses a quantitative approach by collecting data from 60 respondents who are FEB UNISMA students of the class of 2021. This study uses a snowball sampling technique with the help of the WhatsApp application. The variables studied are Green satisfaction, green knowledge and green trust which are one of the important factors in purchasing decisions for environmentally friendly skincare products. The results of this study show that simultaneously green satisfaction, green knowledge and green trust affect the purchase decision of skintific products. Green satisfaction and green knowledge partially affect the purchase decision of skintific products, while green trust has no effect on the purchase decision of skintific products. This study suggests that Skintific companies further evaluate their communication strategies regarding environmentally friendly practices that have been implemented regularly and show their commitment to environmental issues through transparent sustainable actions in an effort to build communication with consumers that will affect green trust. Keywords: Green Satisfaction, Green Knowledge, Green Trust, Purchase Decisions, Skintific Products.